Evaluating the Arm’s Length Principle in Fiscal Corrections for Intragroup Services: Evidence from the Federal Karyatama-EMAPPL Case - Kartiko, Nafis Dwi; Alex Oktobertus Pandapotan Gultom (Siyasah Dusturiyah: State Law Review, 2025)
This study aims to analyze the compatibility between Indonesian domestic norms and the OECD Transfer Pricing Guidelines in the application of the arm's length principle (ALP) on the verification of cross-jurisdictional management service costs. The analysis is based on Tax Court Decision Number PUT-007752.15/2023/PP/M.XIII.B. This study employs a normative-dogmatic legal method to examine the consistency between Indonesian domestic norms and the OECD Transfer Pricing Guidelines in applying the arm’s length principle to cross-jurisdictional management service costs. The analysis integrates statutory, case, and conceptual approaches to ensure systematic coherence between positive law, jurisprudence, and international tax doctrine. Primary legal materials such as tax laws and court decisions provide binding authority, while secondary academic sources offer analytical depth to contextualize Indonesia’s doctrinal alignment within global transfer pricing standards. This study concludes that applying the arm’s length principle (ALP) to cross-jurisdictional management service costs requires balancing legal certainty with economic substance. The PT Federal Karyatama–ExxonMobil Asia Pacific Pte. Ltd. case reveals doctrinal tension between the OECD’s soft law flexibility and Indonesia’s hard law rigidity under PMK 172/2023. The findings indicate a selective convergence model, where Indonesia adopts OECD principles but enforces stricter evidentiary standards, resulting in a conservative, rule-based approach prone to interpretative disputes. This study contributes theoretically to the strengthening of the ALP and practically to the optimization of Advance Pricing Agreements and Mutual Agreement Procedures.